Zastosowanie filmu w projekcie „Niewidzialne miasto” - Kaczmarek, Jerzy (Człowiek i Społeczeństwo, 2013)
Author of this article discusses the various ways of the use of the film materials in the project “Invisible city” and their analysis (four short films about the makers of “Invisible city”, four kinograms of the studied places and one scientific film that is a form of selfreflexion of the researchers). Farther he presents a short historical and theoretical introduction to the scientific film and to his specific genre who is sociological film. For conclusion he undertakes the reflexion about the possibility of the next studies based on the film materials from the project “Invisible city”.